In vitro 3D cell sheet-based model for unraveling scar pathophysiology - Rodrigues, Daniel Barreira (2017)
Fibroblasts are key players in the scarring process. In hypertrophic scars, fibroblasts suffer phenotypical changes into myofibroblasts persisting in the wound under the influence of local biochemical (TGFb1) and biomechanical signaling leading to enhanced immature extracellular matrix (ECM) synthesis. Benchtop models of hypertrophic scars rely on scarce human ex vivo samples or standard 2D cultures of hypertrophic scar fibroblasts. We therefore propose the use of human dermal fibroblast cell sheets (hDFbsCS) as the first step to attain cell sheets with a myofibroblast-like phenotype to generate cohesive in vitro 3D scar-like tissues. hDFbsCS were produced as previously described (Cerqueira, 2014), and stimulated with TGFb1 up to 21 days. Following phenotype and ECM characterization, 3 hDFbsCS were stacked to obtain a 3D structure. Gene and protein analysis showed that upon TGFb1 stimulation, hDFbsCS present a higher expression of aSMA, fibronectin EDA and EDB, characteristic of amyofibroblast-like phenotype. Regarding the expression of scar ECM-associated proteins, TGFb1 stimulated hDFbsCS produced increased fibronectin and collagen I. Upon stacking of hDFbsCS obtained after 7 days of culture in the presence of TGFb1, stable and integrated 3D constructs were obtained. This work suggests that it is possible to create cohesive 3D scar-like tissue structures from hDFbsCS opening the possibility to develop in vitro 3D scar models to study wound healing deregulation pathophysiology. Acknowledgments: Grant IF.00945.2014 and SFRH.BD. 119756.2016 (FCT MCTES), NORTE.08.5369.FSE.000044 (funded by Programa Operacional Norte 2020 Fundo Social Europeu), GENE2SKIN Twinning Project, Horizon 2020 (European Commission).